Pomegranate Peel Extract Activities as Antioxidant and Antibiofilm against Bacteria Isolated from Caries and Supragingival Plaque - BENSLIMANE, Sabria; REBAI, Ouafa; DJIBAOUI, Rachid; ARABI, Abed (Hashemite University, 2019)
The present study aimed to extract polyphenols from pomegranate (Punica granatum L.) peel extract (PPE) by maceration using three different solvants: acetone 70%, ethanol 70% and methanol 70% (v/v). The antioxidant capacity potential was determined by scavenging activity of free radicals (DPPH) and ferric reducing power (FRAP) assays. The antimicrobial activity of PPE was evaluated against six oral pathogens isolated from dental caries and supragingival plaque (Streptococcus mutans, Enterococcus faecalis, Gemella morbillorum, Staphylococcus epidermis, Enterococcus bugandensis and Klebsiella oxytoca). The highest total phenolic and flavonoid contents were obtained with ethanolic PPE (204.67 ± 15.26 26 mg gallic acid equivalents (GAE)/g dry weight (DW), 67.67 ± 1.53 mg quercetin equivalent (QE)/g DW respectively). The highest proanthocyanidin content was observed with acetonic extract (220 ± 17.32 mg catechin equivalent (CE)/g DW). The phenolic profile of ethanolic PPE was determined by HPLC analysis; peduncalagin, punigluconin and punicalagin as a predominant ellagitannin have been identified. The highest scavenging activity (87.37 ± 1.36%) was exhibited by ethanolic PPE with the lowest IC50 value (220 ± 14µg/ml) for DPPH, whereas the highest reducing power assay was observed with acetonic PPE with a value of 1.48 at 700 nm. The antibacterial activity was investigated by microdilution method, all bacteria were sensitive to the extract with MIC (minimum inhibitory concentration) ranging from 0.0125 to 100 mg/ml, the Gram-positive bacteria are the most sensitive. Antibiofilm activity of ethanolic PPE was tested by crystal violet. The maximum biofilm inhibition was observed at the highest concentration of the extract (MIC) with E. faecalis (91.95%) and S. epidermis (90.7%). Results indicate the potential application of PPE as antioxidant and antibacterial agent against oral pathogens and that it has great potential for prevention and treatment of dental caries.
Keywords: Punica granatum peel, polyphenols, antioxidant, oral biofilm, minimum inhibitory concentration (MIC)